Short-term outcomes of transcatheter perimembranous ventricular septal defect closure using the konar-multifunctional occluder: the Taiwanese experience - Liao, Li-Chin; Fu, Yun-Ching; Lee, Pi-Chang; Jan, Sheng-Ling; Lin, Ming-Chih; Chuang, Chieh-Mao; Hung, Hui-Chih (Frontiers in Cardiovascular Medicine, 2025)
IntroductionTranscatheter device closure of perimembranous ventricular septal defect (PmVSD) using the Lifetech KONAR-MF ventricular septal defect occluder (MFO) presents a promising and effective alternative to surgical repair.ObjectivesThis study aims to evaluate the 6-month safety and efficacy of the MFO device for PmVSD closure.Materials and methodsWe conducted a retrospective analysis of clinical data from patients who underwent percutaneous PmVSD closure using the MFO device at our institution between December 2021 and June 2024. Safety, procedural and 6-month outcomes were systematically assessed.ResultsA total of 115 patients (52.2% male) underwent transcatheter PmVSD closure. The median age was 7.6 years [interquartile range (IQR), 4.0–27.2] and weight 25.6 kg (IQR, 14.2–62.6). Median defect size by angiography was 5.7 mm (IQR, 3.8–8.3) on the left ventricle side and 3.3 mm (IQR, 2.3–4.4) on the right ventricle side. Aortic valve prolapse (AVP) was noted in 114 patients (99.1%), with pre-procedural aortic regurgitation (AR) in 36 (31.3%). Median pulmonary artery pressure was 17 mmHg (IQR, 14–20); 48 (41.7%) had Qp/Qs >1.5. All procedures were successful; 33 (28.7%) used a retrograde approach. Median fluoroscopy time was 22 min (IQR, 15–33). Complete closure was achieved in 51.3% at 1 day, 62.6% at 1 month, 69.6% at 3 months, and 83.5% at 6 months. Transient conduction disturbances (n = 4), hypotension (n = 1), and femoral hematoma (n = 1) were observed. No cases of endocarditis, valve injury, or complete atrioventricular block occurred.ConclusionTranscatheter closure of PmVSD with the MFO demonstrated safety and efficacy during the 6-month follow-up period. Notably, the majority of defects in this cohort were small in size.